Recent measurements of compact electronically tunable liquid crystal phase shifter in rectangular waveguide topology. Issue 21 (1st October 2013) - Weickhmann, C.; Nathrath, N.; Gehring, R.; Gaebler, A.; Jost, M.; Jakoby, R.
Abstract : A low‐weight, compact, tunable phase shifter based on liquid crystal technology is presented. It is designed in a hollow waveguide topology with a dielectric filled cross‐section. The operational frequency range is 21–29 GHz, but data up to 35 GHz have been obtained and are presented. The device offers more than 140° phase shift peak per dB insertion loss and 110–130°/dB in the desired range.